Large Sample Neutron Activation Analysis for Cultural Heritage Studies - Vasilopoulou, T.; Tzika, F.; Stamatelatos, I. E. (HNPS Advances in Nuclear Physics, 2012)
Large Sample Neutron Activation Analysis (LSNAA) is a non-destructive, multi-element analysis technique with a broad range of scientific and technological applications. Since both neutrons and gamma rays have penetration depths of the order of several centimeters within materials, depending on their energy and sample material properties, LSNAA enables non-destructive compositional analysis of the inner structure of large volume samples (up to several litters in volume). In this work, applications of LSNAA in cultural heritage studies are presented and the unique capabilities of the technique for bulk sample elemental analysis of precious and archaeological objects that need to be preserved intact and cannot be damaged for sampling purposes are discussed.